1954
DOI: 10.1071/bi9540282
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Sources of Some Australian Mosquitoes

Abstract: SummaryThe results of over 1400 precipitin tests on the stomach contents of engorged mosquitoes to determine the source of their blood meals are recorded. Fifteen species of mosquitoes are included in this survey, but three .species, Anopheles annulipes, Culex fatigans, and C. annulirostris, dominated the collections.Engorged mosquitoes have been collected from three types of situation. (i) Restricted animal habitats such as human dwellings, fowl houses, horse stables, dog kennels, and rabbit warrens; (ii) The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1958
1958
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 6 publications
2
32
0
Order By: Relevance
“…quinquefasciatus on a diversity of avian and mammalian hosts ( N = 34), consistent with the results of previous studies. [39][40][41][42][43][44][45][46] Nevertheless, the actual ratio of avian and mammalian feedings varied considerably among various geographic sites. Human-derived blood meals constituted 1.9% of all vertebrate-derived blood meals, indicating that Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…quinquefasciatus on a diversity of avian and mammalian hosts ( N = 34), consistent with the results of previous studies. [39][40][41][42][43][44][45][46] Nevertheless, the actual ratio of avian and mammalian feedings varied considerably among various geographic sites. Human-derived blood meals constituted 1.9% of all vertebrate-derived blood meals, indicating that Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of 65 engorged female Cx. erythrothorax collected by EVS light traps revealed that 56.9% ( N = 37), 40.0% ( N = 26), and 3.1% ( N = 2) of mosquitoes acquired blood meals from birds, mammals, and from mixed bird blood meals, respectively ( Table 3 ). Host variability was relatively high, with 21 different avian and mammalian species represented in 67 feedings from 15 (2 riparian and 13 wetland) collection sites.…”
mentioning
confidence: 99%
“…detritus, 15 Culiseta annulata, 12 M. richiardii and 1 C. morsitans were caught (Service, 1969 b An alternative method to using traps for determining whether mosquitoes feed on rabbits is to identify by precipitin tests blood-meals of engorged mosquitoes collected from natural resting places. Lee, Clinton & O'Gower (1954) Six hundred and fifty-five blood-smears from 14 species were tested and 58 of these from six species were positive for rabbit blood. It is just conceivable, though I consider it most unlikely, that these feeds on rabbits were from lethargic animals suffering from myxomatosis, and that mosquitoes cannot feed on healthy active wild rabbits.…”
Section: Tethered Rabbitsmentioning
confidence: 99%
“…This is complementary to the field findings of MYERS (1954) andMYERS et al (1954) that the same two species of mosquitoes are primary vectors of the disease in epizootics while other species not feeding on rabbits do not contribute to the spread of infection although capable of doing so experimentally. Similarly the isolations of avian pox viruses from 0. annulirostris, Culex fatigans and probably Culex pipiens australicus are supported by the aviophilic findings for these species by LEE et al (1954). Association of representatives of the Culex pipiens complex with avian pox viruses has usually been explained by their preference for bird blood (KLIGLER and ASCHNER, 1931;FRENCH and REEVES, 1954).…”
Section: Mechanical Transmissionmentioning
confidence: 74%
“…Subsequent studies have confirmed a surprising degree of vector specificity largely controlled by host feeding preference. The recent study by LEE et al (1954) of blood sources of Australian mosquitoes shows that Anopheles annulipes and Culex annulirostris have a strong preference for rabbit blood. This is complementary to the field findings of MYERS (1954) andMYERS et al (1954) that the same two species of mosquitoes are primary vectors of the disease in epizootics while other species not feeding on rabbits do not contribute to the spread of infection although capable of doing so experimentally.…”
Section: Mechanical Transmissionmentioning
confidence: 99%